Abdomen and thoracic imaging : an engineering & clinical perspective - Saba, Luca; Suri, Jasjit; El-Baz, Ayman S. (Springer US, 2014)
Ayman El-Baz, Ph.D., Associate Professor in the Department of Bioengineering at the University of Louisville, KY. Dr. El-Baz has fourteen years of hands-on experience in the fields of bioimaging modeling and computer-assisted diagnostic systems. His work has been reported at several prestigious international conferences (e.g., CVPR, ICCV, MICCAI, ISBI, etc.) and in journals (e.g., IEEE TMI, IEEE TIP, IEEE TBME, IEEE TITB, Brain, NMR, etc.). Dr. El-Baz has authored or coauthored more than 300 technical articles. Luca Saba, MD, is a researcher in the field of Multi-Detector-Row Computed Tomography, Magnetic Resonance, Ultrasound, Neuroradiology, and Diagnostic in Vascular Sciences. His works, as lead author, achieved more than 100 high impact factor, peer-reviewed Journals. He is well known speaker and has spoken over 45 times at national and international levels. Dr. Saba has won 12 scientific and extracurricular awards during his career. Jasjit S. Suri, MS, PhD, MBA is an innovator, visionary, scientist, and an internationally known world leader in the field of Healthcare Imaging and biomedical devices. Dr. Suri was the recipient of Director General's Gold medal in 1980 and the Fellow of American Institute of Medical and Biological Engineering (AIMBE), awarded by National Academy of Sciences, Washington DC in 2004. Dr. Suri has been the chairman of IEEE Denver section, has won over 50 awards during his career including project, program and regulatory management, and has held several executive positions.